Understanding the impact of water management on people for investment in sustainable infrastructure in the UK. Issue 2 (18th July 2017) - Cambridge, Adam; Gill, Andy; Barker, Monica; Tant, Max; Simmonds, Carolann; Watt, Nathan
Abstract : This study explored whether digital footprinting through the use of mobile data could be used to improve the understanding of water and environmental events on people, to enhance the evidence base for investment in sustainable infrastructure. The study focused on Margate, UK, where an integrated stakeholder surface water management plan was being developed to support the town's regeneration and urban growth aspirations. The objectives were to assess ( a ) the usefulness of mobile data in infrastructure studies and ( b ) the impacts of a recent water pollution and beach closure event on visitor footfall to and from Margate. It was found that digital footprinting techniques provided substantial new insight into human dynamics (spatially, temporally, and demographically) with visitor footfall to and from Margate strongly driven by weather, predominately from the local area and over 65 years of age, but with 16% of visitors from London. With further work (longer time periods, further population data, and statistical analysis) digital footprinting techniques could give Margate's regeneration strategy an area to focus on in diversifying its economy and reliance on tourism, as well as moreover, a basis for future infrastructure appraisal and evaluation in the UK (potentially in real time). The development of the latter will pose many of the real privacy challenges that previous study has highlighted and is likely to be pursued due to the current financial climate needing to deliver better services for lower cost.